Pengembangan Model Pelatihan Tenaga Kerja Sektor Informal di Dinas Tenaga Kerja Transmigrasi dan Kependudukan Kabupaten Aceh Tenggara - Tri Rasid Desky; Fitra Jaya (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
This study aims to describe how the stages of implementation stream training informal sector workers in labor offices transmigration province of East Java in the expansion work, analyze the obstacles encountered in the planning of the training program, as well as modeling appropriate training in accordance with conditions on the ground and input from various parties, this research use descriptive qualitative research methods, techniques determination of informants using purposive sampling, these techniques have been because the researcher wants to focus on parties who know the conditions on the ground. Results from this study is the first training conducted regularly and the classical, the purpose of training has reached short-term goals in training but in the long term they need more motivation for the trainees, second, obstacle training during implementation consists of matter and the overcrowded curriculum tend to be the same as the previous training, time constraints, participation is not optimal, overall, limited time, resources and costs in the post-training evaluation and monitoring, the third development training model has not been implemented in this training.